2016
DOI: 10.1017/thg.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of HSD17B1 Ser312Gly with Cancer Risk: Evidence from 66,147 Subjects

Abstract: Hydroxysteroid (17-beta)dehydrogenase 1(HSD17B1) plays a central role in sex steroid hormone metabolism. HSD17B1 polymorphic variants may contribute to cancer susceptibility. Numerous investigations have been conducted to assess the association between HSD17B1 Ser312Gly polymorphism and cancer risk in multiple ethnicities, yet these have produced inconsistent results. We therefore performed this comprehensive meta-analysis to attempt to provide a quality assessment of the association of interest. Odds ratios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…They include development of the risk of endometrial and breast cancer [31, 3335]. The meta-analysis did not show significant association between HSD17B1 rs605059 gene polymorphisms and risks of endometrial cancer [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They include development of the risk of endometrial and breast cancer [31, 3335]. The meta-analysis did not show significant association between HSD17B1 rs605059 gene polymorphisms and risks of endometrial cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis did not show significant association between HSD17B1 rs605059 gene polymorphisms and risks of endometrial cancer [31]. Additionally, the recent meta-analysis conducted by Shi et al (2016) suggested that the HSD17B1 937 G allele may protect from breast cancer development in Caucasians, but not among Asians [35]. …”
Section: Discussionmentioning
confidence: 99%
“…The impact of HSD17B polymorphisms appears limited. A recent meta-analysis on the impact of HSD17B1 polymorphism rs605059 shows that it might confer genetic cancer susceptibility in Caucasians, but authors propose more studies are needed [77]. On the other hand, the SNP rs4445895_T was shown to be associated with lower intratumoral HSD17B2 mRNA levels and inversely correlated with E2 levels [78], indicating that HSD17B2 polymorphisms may have clinical relevance.…”
Section: Control Of Expression and Regulation Of Hsd17b1 And Hsd17b2mentioning
confidence: 99%
“…Polymorphisms in the CYP19A1 gene that encodes aromatase, an enzyme that converts androgens to oestrogens, were shown to be associated with serum sex hormone levels in Japanese people (11)(12)(13) . The rs605059 polymorphism in the HSD17B1 gene that encodes 17β-hydroxysteroid dehydrogenase type 1 (17β-HSD1), which catalyses the synthesis of E2 from oestrone (E1), has been investigated regarding its association with multiethnic breast cancer risk (14,15) .…”
mentioning
confidence: 99%